2009
DOI: 10.1007/s11010-009-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 transcription in the postnatal brain is regulated by a bHLH transcription factor Math2 through an E-box sequence in the 5′-UTR of the gene

Abstract: YB-1 controls gene expression at both the transcriptional and translational levels. In the brain, a high level of YB-1 is expressed from prior to the first week after birth. However, YB-1 expression substantially declines to the adult level thereafter. Here, we investigated the regulatory mechanism of YB-1 transcription in the postnatal brain. We found that an E-box sequence within the 5'-untranslated region (5'-UTR) of the gene was recognized by Math2 in the 5-day-old brain, whereas the DNA binding was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We have reported that YB-1 transcription in the postnatal brain is regulated by a transcription factor, Math2 (Ohashi et al 2009b). This indicates that a high level of YB-1 is supplied to the cytoplasm of neurons in the developing brain to regulate the synthesis of proteins such as GluR2 and CaM1, thereafter declining to a much lower level that may be sufficient to maintain the established nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that YB-1 transcription in the postnatal brain is regulated by a transcription factor, Math2 (Ohashi et al 2009b). This indicates that a high level of YB-1 is supplied to the cytoplasm of neurons in the developing brain to regulate the synthesis of proteins such as GluR2 and CaM1, thereafter declining to a much lower level that may be sufficient to maintain the established nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Since YB-1 performs many functions in the cell and participates in its crucial events, synthesis of this protein must be under strict control. There are reports that the following transcription factors are involved in regulation of transcription of the YB-1 gene: Twist, 36 GATA, 37 Math2 (Neurod6), 38 p73, c-Myc и Max. 39 A few studies have been reported on regulation of YB-1 synthesis at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of YB-1 is embryonically lethal for mice where major developmental defects were reported in the brain (6,7), yet the molecular mechanism underlying this is unknown. Although it is downregulated at postnatal life (8), it is highly expressed in cancer where its expression is associated with poor prognosis (4). YB-1 was highly expressed in gliomas when compared with surrounding normal brain tissues (9).…”
Section: Introductionmentioning
confidence: 99%